Analisis Efektivitas Pajak Reklame Terhadap Pendapatan Asli Daerah Kota Malang Tahun 2018-2024 - Indrawati, Putri Belia; Della Afita Khaerunnisa; Luthfia Noor Aziza; Nora Aulia Hidayatul; Syehta Maulia Tara (Public Administration Dept, Faculty of Social and Political Science, 2025)
Advertising tax is a vital component of Malang City's Local Revenue (PAD), offering significant potential due to its clear tax objects and minimal tax avoidance. Malang City, as a rapidly growing economic center in East Java, shows high use of advertising media, making it a strategic source of local revenue. This study analyzes the effectiveness of advertising tax collection on the PAD of Malang City from 2018 to 2024. A descriptive quantitative approach was used, with secondary data from the Regional Revenue Agency (Bapenda) of Malang City and the Malang City APBD realization reports for the 2018-2024 period as the basis for analysis. Effectiveness was measured by comparing the realization of advertising tax revenue with the target set using the formula: Effectiveness = (Realization of Advertising Tax Revenue / Advertising Tax Revenue Target) x 100%. The analysis results show fluctuations in effectiveness, with 2018 and 2019 showing “highly effective” effectiveness (105.01% and 126.16%) because the realization exceeded the target. However, in 2020, 2021, 2022, 2023, and 2024, effectiveness declined to “less effective” (68.89%, 72.62%, 78.57%, 73.19%, and 82.11%, respectively), mainly due to the COVID-19 pandemic, which had a significant impact on economic activity and revenue targets. Despite a positive post-COVID-19 trend, the level of effectiveness has not returned to the “highly effective” level seen before the pandemic. This study is expected to serve as a reference for the Malang City Revenue Agency in evaluating performance and formulating better fiscal policies in the future.